2021
DOI: 10.1101/2021.11.03.21265791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohort study of Covid-19 vaccine effectiveness among healthcare workers in Finland, December 2020 - October 2021

Abstract: Recently, Covid-19 vaccine effectiveness has decreased especially against mild disease due to emergence of the Delta variant and waning protection. In this register-based study among healthcare workers in Finland, the vaccine effectiveness of two-dose mRNA vaccine series against SARS-CoV-2 infection decreased from 82% (95% CI 79-85%) 14-90 days after vaccination to 53% (43-62%) after 6 months. Similar trend was observed for other series. Waning was not observed against Covid-19 hospitalization. These results f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Recent studies showed 86-88% vaccine-associated reduction in the hospital admission rate in those infected with the delta VOC 1921 ; Our observations confirm the positive impact of vaccination on the severity of the SARS-CoV-2 delta infection, even in hospitalised patients. Moreover, we observed that the positive impact was maintained in populations at risk of severe Covid-19: those aged over 65 years, and those with pre-existing cardiac failure, kidney failure, or a chronic respiratory disease (at least for one or several severity criteria).…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies showed 86-88% vaccine-associated reduction in the hospital admission rate in those infected with the delta VOC 1921 ; Our observations confirm the positive impact of vaccination on the severity of the SARS-CoV-2 delta infection, even in hospitalised patients. Moreover, we observed that the positive impact was maintained in populations at risk of severe Covid-19: those aged over 65 years, and those with pre-existing cardiac failure, kidney failure, or a chronic respiratory disease (at least for one or several severity criteria).…”
Section: Discussionsupporting
confidence: 86%
“…Three studies were randomised controlled trials 19 , 20 , 21 and 15 were post-introduction observational studies (seven were test-negative design case-control studies, six were retrospective studies, and two were prospective cohort studies; table 1 ). 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Studies were done in Canada (one study), Finland (one study), Israel (one study), Qatar (one study), Spain (one study), Sweden (one study), the UK (two studies), the USA (eight studies), and in addition two multicountry clinical trials were carried out. The Canadian study included separate results for Quebec and British Columbia; therefore, the results for each province were considered separately for this review.…”
Section: Resultsmentioning
confidence: 99%
“…12 studies evaluated the vaccine efficacy or effectiveness over time for severe COVID-19 disease, among which there were 36 vaccine-specific analyses (Pfizer–BioNTech-Comirnaty, n=19; Moderna-mRNA-1273, n=10; Janssen-Ad26.COV2.S, n=4; AstraZeneca-Vaxzevria, n=3; table 1 ). 10 , 21 , 22 , 24 , 25 , 27 , 28 , 29 , 31 , 32 , 33 , 34 13 vaccine-specific analyses took place in single-variant settings (11 in delta settings and two in Alpha settings), and 23 analyses took place in mixed-variant settings. 22 vaccine-specific analyses were done among people of all ages and 14 among older people.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with other studies investigating waning of vaccine effectiveness, as summarised through a systematic review by Feikin et al 21 Most observational studies employ a testnegative study design, while some are register-based cohort studies like ours. 19,[25][26][27][28][29][30][31][32][33] We reported large waning of effectiveness against SARS-CoV-2 infection, which could have several explanations. First, we have a longer follow-up time than previously published studies.…”
Section: Discussionmentioning
confidence: 99%